Gait abnormalities in chronic fatigue syndrome - Boda, Wanda L.; Natelson, Benjamin H.; Sisto, Sue Ann; Tapp, Walter N. (Journal of the neurological sciences, 1995)
To evaluate our clinical impression that patients with the chronic fatigue syndrome (CFS) did not walk normally, we assessed gait kinematics at slow walking speeds (i.e., 0.45, 0.89 and 1.34 m/sec) and 30 m run time speeds on CFS patients and on a comparison group of sedentary controls. Run time was significantly slower for CFS than control subjects ( p < 0.001). There was a significant interaction ( p < 0.01) between group and speed for maximum hip angle during stance and swing phase with hip angle being significantly larger at 1.34 m/sec for CFS than controls subjects for both cases ( p < 0.05). Knee flexion during stance and swing phases was significantly larger for controls than CFS subjects at 0.45 m/sec ( p < 0.01). Ratio of stride length divided by leg length was significantly larger for the control subjects than for the CFS subjects with differences occurring at 0.45 and 0.89 m/sec ( p < 0.01) but not 1.34 m/sec. The data indicate that CFS patients have gait abnormalities when compared to sedentary controls. These could be due to balance problems, muscle weakness, or central nervous system dysfunction; deciding which will require further research. Evaluation of gait may be a useful tool to measure outcome following therapeutic interventions.